(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the significant influence of interactive games on the acquisition of English vocabulary among second language learners. It critically examines how engaging game-based activities foster a more dynamic and effective learning environment compared to traditional methods. The discussion covers the psychological and pedagogical benefits of gamification, including enhanced motivation, reduced anxiety, and improved memory retention through contextualized learning and repeated exposure. The article also provides insights into various types of interactive games, both digital and non-digital, and their practical implementation in diverse educational settings to optimize vocabulary development.